Prohormone convertase 2 activity is increased in the hippocampus of Wfs1 knockout mice - Tein, Karin; Kasvandik, Sergo; Kõks, Sulev; Vasar, Eero; Terasmaa, Anton (Frontiers in Molecular Neuroscience, 2015)
Background Mutations in WFS1 gene cause Wolfram syndrome, which is a rare autosomal recessive disorder, characterized by diabetes insipidus, diabetes mellitus, optic nerve atrophy and deafness (DIDMOAD). The WFS1 gene product wolframin is located in the endoplasmic reticulum. Mice lacking this gene exhibit disturbances in the processing and secretion of peptides, such as vasopressin and insulin. In the brain, high levels of the wolframin protein have been observed in the hippocampus, amygdala and limbic structures. The aim of this study was to investigate the effect of Wfs1 knockout on peptide processing in mouse hippocampus. A peptidomic approach was used to characterize individual peptides in the hippocampus of wild-type and Wfs1 knockout mice. Results We identified 126 peptides in hippocampal extracts and the levels of 10 peptides differed between Wfs1 KO and wild-type mice at P<0.05. The peptide with the largest alteration was little-LEN, which level was 25 times higher in the hippocampus of Wfs1 KO mice compared to wild-type mice. Processing (cleavage) of little-LEN from the Pcsk1n gene product proSAAS involves prohormone convertase 2 (PC2). Thus, PC2 activity was measured in extracts prepared from the hippocampus of Wfs1 knockout mice. The activity of PC2 in Wfs1 mutant mice was significantly higher (149.9±2.3%, p<0.0001, n=8) than in wild-type mice (100.0±7.0%, n=8). However, Western blot analysis showed that protein levels of 7B2, proPC2 and PC2 were same in both groups, and so were gene expression levels. Conclusions Processing of proSAAS is altered in the hippocampus of Wfs1-KO mice, which is caused by increased activity of PC2. Increased activity of PC2 in Wfs1 knockout mice is not caused by alteration in the levels of PC2 protein. Our results suggest a functional link between Wfs1 and PC2. Thus, the detailed molecular mechanism of the role of Wfs1 in the regulation of PC2 activity needs further investigation.